A novel colorimetric fluoride sensor based on a semi‐rigid chromophore controlled by hydrogen bonding. (18th March 2015) - Li, Jiling; Xu, Xiaoyong; Shao, Xusheng; Li, Zhong
Abstract: A novel semi‐rigid latent chromophore E1, containing an amide subunit activated by an adjacent semi‐rigid intramolecular hydrogen‐bonding (IHB) unit, was designed for the detection of fluoride ion by the 'naked‐eye' in CH3 CN. Comparative studies on structural analogs (E2, E3, and E4) provided significant insight into the structural and functional role of the amide N–H and IHB segment in the selective recognition of fluoride ions. The deprotonation of the amide N–H followed by the enhancement of intramolecular charge transfer (ICT) induced the colorimetric detection of E1 for fluoride ion. Copyright © 2015 John Wiley & Sons, Ltd.